PENEGAKAN HUKUM PIDANA TERHADAP PENGGUNA NARKOTIKA SEBAGAI PELAKU TINDAK PIDANA NARKOTIKA DI POLRESTA MEDAN - Victor Ziliwu; Syafruddin Kalo; Mahmud Mulyadi; Madiasa Ablisar (Universitas Sumatera Utara, 2016)
ABSTRACT Law on Narcotics and Psychotropic Substances Act mandates an obligation to undergo treatment and the treatment and rehabilitation of drug addicts. The provisions concerning the